Réponses

Meilleure réponse !
2014-06-15T16:38:54+02:00
7 - 5 ( 2x + 1 )( 8 - 4x )( 2x + 9 )
= 7 - [ ( 10x + 5 )( 8 - 4x )( 2x + 9 ) ]
= 7 - [ ( 80x- 40x² + 40 - 20x )( 2x + 9) ]
= 7 - [ ( -40x² + 60x + 40 )( 2x + 9) ]
= 7 - [ ( -80x3 - 360x² + 120x² + 540x + 80x + 360) ]
= 7 - ( -80x3 - 240x² + 620x + 360)
= 7 + 80x3 + 240x² - 620x - 360
= 80x3 + 240x² - 620x - 353
cela correspond-t-il à votre résultat?
oui merci
avec plaisir
2014-06-15T16:42:20+02:00
7-(19x-5)(16x+72-8x^2-36x)
7-(10x-5)(-20x-8x^2+72)
7-(-200x^2-80x^3+720x+100x-40x^2+360
7+200x^2+80x^4-720x-100x-40x^2+360
80x^3 + 160x^2-820x +367